2011
DOI: 10.1073/pnas.1015938108
|View full text |Cite
|
Sign up to set email alerts
|

Retaining cell–cell contact enables preparation and culture of spheroids composed of pure primary cancer cells from colorectal cancer

Abstract: Primary culture of the cancer cells from patients’ tumors can provide crucial information of individual tumors, yet the technology has not been optimized until now. We developed an innovative culture method for primary colorectal cancer cells, based on the principle that cell–cell contact of cancer cells was maintained throughout the process. When tumor tissue was dissociated into cell clusters, in which cell–cell contact was retained, they rapidly formed spheroids that we termed cancer tissue-originated spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
360
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 285 publications
(383 citation statements)
references
References 36 publications
16
360
1
6
Order By: Relevance
“…Collagen gel was composed of cell-matrix type I-A (Nitta Gelatin, Osaka, Japan):10 Â DMEM (Sigma, Saint Louis, MO, USA):reconstitution buffer (50 mM NaOH, 260 mM NaHCO 3 , 200 mM HEPES) at a ratio of 8:1:1 (vol/vol/vol). In this study, we used two different CTOS spheroid lines (C45 and C132), which were obtained from two patients with colorectal cancer used in the previous study [24], expanded via transplantation into mice, and maintained with reported procedures [24] (Table S2). To seed cells evenly onto the NCPs, the obtained CTOS spheroids were mono-cellularized using the following procedures.…”
Section: Cancer Tissue-originated Uniformed Spheroid Assay (Cousa)mentioning
confidence: 99%
See 2 more Smart Citations
“…Collagen gel was composed of cell-matrix type I-A (Nitta Gelatin, Osaka, Japan):10 Â DMEM (Sigma, Saint Louis, MO, USA):reconstitution buffer (50 mM NaOH, 260 mM NaHCO 3 , 200 mM HEPES) at a ratio of 8:1:1 (vol/vol/vol). In this study, we used two different CTOS spheroid lines (C45 and C132), which were obtained from two patients with colorectal cancer used in the previous study [24], expanded via transplantation into mice, and maintained with reported procedures [24] (Table S2). To seed cells evenly onto the NCPs, the obtained CTOS spheroids were mono-cellularized using the following procedures.…”
Section: Cancer Tissue-originated Uniformed Spheroid Assay (Cousa)mentioning
confidence: 99%
“…To construct the NCP drug screening system with cells derived from patient cancer tissues, patient-derived original cancer spheroids obtained by a recentlydeveloped CTOS method [24] were used. Briefly, colorectal cancer specimen samples were obtained from patients at the Osaka Medical Center for Cancer and Cardiovascular Diseases.…”
Section: Cancer Tissue-originated Uniformed Spheroid Assay (Cousa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Undigested debris was removed by a 1,000- as well as a 500-μm nylon mesh, and finally cell clumps that did not pass through 100-μm nylon mesh were collected for primary culture [12]. The cell clumps formed cancer cell spheroids or otherwise became attached to the plastic dish on the following day with a success rate of almost 100% [12].…”
Section: Methodsmentioning
confidence: 99%
“…Undigested debris was removed by a 1,000- as well as a 500-μm nylon mesh, and finally cell clumps that did not pass through 100-μm nylon mesh were collected for primary culture [12]. The cell clumps formed cancer cell spheroids or otherwise became attached to the plastic dish on the following day with a success rate of almost 100% [12]. The culture medium was serum-free advanced DMEM/F-12 (GIBCO) supplemented with FGF-2 (10 ng/ml; ReproCell, Yokohama, Japan), ROCK inhibitor [13] (Y-27632, 10-20 μ M ; Wako Pure Chemical, Osaka, Japan), penicillin (100 mg/ml; Wako), streptomycin (0.1 mg/ml; Wako), gentamicin (50 μg/ml; Wako) and Fungizone (2.5 μg/ml; GIBCO).…”
Section: Methodsmentioning
confidence: 99%